JEAN BODIN'S NOTION OFSOVEREIGNTY, GOOD GOVERNANCE AND NTHE QUEST FOR SOCIOPOLITICALADVANCEMENT IN NIGER - EKUASE INNOCENT O.; COLLINS OKONKWO; EDOGIAWERIE MORRIS K.O. (International Studies Journal)
Bodin's far reaching analysis on the sovereign state and good governance shows that he did not miss words when he recommended that the management of the state shouldbe separated from the management of the church. He insists that the matters of the state are not the same, in many ramifications, with matters of the church. He argues that matters of the church are distinct and unique compared to that of the state. The church is supposed to be a sacred institution which should concern itself with issues that pertain to spirituality, theology, heaven, etc.Bodin does not concur with the idea where church fathers (Priests) would be directly involved with matters that do not concern the church and its administration but focus on issues that concern thestate and its administration. For Bodin, it is an aberration for church fathers to delve into and perpetrate themselves in matters that don't concern the church and its administration.He concurs with Platothat the business of state (Administration) is not a child's play but a very serious business that requires absolute focus and expertise otherwise the essence of the tacit consent would be highly compromised. Bodin strongly maintains, like Plato, that those to be charged with the responsibility of rulership should be properly trained and oriented towards that direction for the sake and essence of effective and efficient administration. This is against the very fact that the church has a very strong hold on the people so much so that citizens are more prepared to obey the church and pay heed to their instructions before the state. The religious nature of men proves this fact all the time. It is based on this premise that this paper attempts to examine Bodin's recommendations on the separation of the church from the state for the purposes of sovereign, good and progressive governance. Can the state actually thrive and survive without the involvement of the church in the running of the day-to-day activities of the state? Could it be that if the church interferes and is directly involved in the administration of the state that good, effective and efficient governance can be attainable especially as far as Nigeria concerned? Would it be possible for the state to retain its sovereignty if the church were to be involved in the running of the affairs of the state? For the sake of an objective and indepth analysis the a priori analytic approach will adopted in this examination.